2016
DOI: 10.1590/0103-8478cr20150047
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of Bt proteins expressed in different structures of transgenic corn against Spodoptera frugiperda

Abstract: Spodoptera frugiperda (J. E. Smith) is the main target pest of Bt corn technologies, such as YieldGard VT PRO™ (Cry1A.105/Cry2Ab2) and PowerCore™ (Cry1A.105/Cry2Ab2/ Cry1F)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Some larvae fail to complete their life cycle due to toxicity of B. thuringiensis. Bernardi et al (2016) reported that 49% of treated S. frugiferda larvae could not complete their life cycle. Figure 1.…”
Section: Mortality=mentioning
confidence: 99%
“…Some larvae fail to complete their life cycle due to toxicity of B. thuringiensis. Bernardi et al (2016) reported that 49% of treated S. frugiferda larvae could not complete their life cycle. Figure 1.…”
Section: Mortality=mentioning
confidence: 99%
“…Of the total area planted with corn and soybean in this country, 79% and 62% express Bt toxins, respectively (Agroconsult, 2018). In addition to corn and soybean, the Brazilian landscape also has cotton and sugarcane expressing Bt toxins, which, in addition to tropical conditions that provide ideal temperature and environmental conditions for insects to undergo multiple generations in a year and multiple plantings of Bt crops in a year, create a scenario favoring rapid resistance evolution (Bernardi et al, 2016; Fatoretto et al, 2017). Several Lepidoptera of economic importance have developed field‐evolved resistance to Bt toxins in Brazil, and major concerns are associated with feeding by fall armyworm, Spodoptera frugiperda (J.E.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to biotic factors that favor resistance, Brazil has a different regulatory system for refuge compliance of regulations in other geographies (Carrière et al, 2020). In Brazil, the National Technical Committee for Biosafety (CTNBio) assesses the biosafety of modified crops, but it does not evaluate or regulate issues related to resistance management, and IRM is not mandatory (Bernardi et al, 2016; Carrière et al, 2020). Resistance management practices for Bt crops are promoted by technology providers and academic and government researchers (e.g., EMBRAPA) (CIB, 2018; IRAC, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several populations of S. frugiperda that are resistant to synthetic insecticides (Almeida et al, 2017;Gutiérrez-Moreno et al, 2019;Boaventura et al, 2020), as well as to Bt corn, are used to control caterpillars (Bernardi et al, 2016;Boaventura et al, 2020). However, further researches are necessary to find other efficient ways for controlling that pest, in order to obtain acceptable and economical levels of agricultural yield in a sustainable way.…”
Section: Introductionmentioning
confidence: 99%